VOLUME 7, NO 1 (2019) - In Chief, Editor (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
Dear readers, Aro, the Scientific Journal of Koya University, is closing its twelve issue (Vol VII, No 1, 2019). It has been a challenging, exciting and yet progressive season for our journal. Aro is publishing its 7th issue as an internationally listed Scientific Journal in Kurdistan Region of Iraq. Notably, Aro has been accepted for indexing in the Emerging Sources Citation Index (ESCI), a new edition of Web of Science™ as of Feb 2016. Content in this issue is under consideration by Clarivate to be accepted in the Science Citation Index Expanded™ (SCIE) during 2019. Aro’s individual articles are currently listed by Clarivate using articles unique DOI numbers which is a historical achievement for our academic community. Aro is starting its seventh-year journey in leading the quality of regional scientific publications with global impact. The editorial team have been working tirelessly to keep the novel mission and sustain Aro’s future publications with greater impacts and citations. It is exciting that Aro has been awarded to DOAJ Seal listing which is an indication of a trusted high standard open access scientific work that so far has allocated to 88 journals worldwide only. The upcoming new season will be an even more exciting period in Aro’s life as Thomson Reuters will examine our journal for a full permanent listing. Aro continues its mission to provide resources, support and advice for researchers in the process of publishing their scientific papers with a global standard quality for an internationally recognised scientific publication, while at the same time offering free public access to scientific research by open online access. This is a daunting task which we hope to advance in the years to come. Thus, in the sections to follow, we would like to share and elaborate on the core elements that constitute Aro. However, finding reliable and skilled reviewers remain a big challenge for us. Aro was created with a long-term vision of becoming accessible to all researchers in Kurdistan and beyond, and covering a wide range of scholarly disciplines in the sciences. Aro is a peer-reviewed, open access journal that publishes original scientific research, global news, letters and commentary as well as review articles in areas of natural sciences and technology. In this issue, you will have access to original research papers in a variety of areas, such as Physics, Chemistry, Biology, Material Science, Civil Engineering, Architectural Engineering, Software Engineering, Electrical and Electronics Engineering, Petroleum Engineering and Geology. The great responses from researchers, academics and professionals in the last five years have made us create a wider Editorial Board which serves the wider submitted scientific manuscripts. However, it is clear that having a dedicated and well-organised editorial board for the journal is only one side of the coin. The other is the ability to attract submissions of quality research and scholarly work. We are thankful to all of those who put their trust in Aro and presented their original research work for publication in Vol VII, No 1 (2019)of the journal, as well as, our thanks are extended to the 23 peer-reviewers from the Universities worldwide for their efforts in reviewing and enabling this issue of Aro. Your support and feedback are invited and appreciated. Dilan M. Rostam Editor-in-Chief Wali M Hamad Executive Publisher Dilan M. Rostam, Salah I. Yahya, Basim M. Fadhil, Fahmi F. Muhammad, Mohammed H.S. Zangana, Jorge Correia, Fouad Muhammad and Nadhir Al-Ansari Executive Editorial Board